2009
DOI: 10.1038/ijo.2009.244
|View full text |Cite|
|
Sign up to set email alerts
|

The prognostic impact of general and abdominal obesity in peripheral arterial disease

Abstract: Objective: Obesity is an independent cardiovascular risk factor, but its prognostic role in patients with peripheral arterial disease (PAD) is not well defined. Accordingly, we assessed the impact of body mass index (BMI) and waist circumference (WC) on cardiovascular risk in a homogeneous cohort of PAD patients. Methods: BMI and WC were measured in 190 consecutive PAD patients with ABI o0.90, referred to our university hospital for intermittent claudication. The occurrence of cardiac, cerebrovascular and peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 44 publications
0
20
2
Order By: Relevance
“…The various studies that assessed the association between obesity and vascular events and mortality in PAD patients report different types of relationship, varying from positive relations 10,24 to an obesity paradox. 25 Although obesity altered the risk for vascular mortality and all-cause mortality in CAD and PAD patients, no relationship between obesity and mortality was observed in CVD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The various studies that assessed the association between obesity and vascular events and mortality in PAD patients report different types of relationship, varying from positive relations 10,24 to an obesity paradox. 25 Although obesity altered the risk for vascular mortality and all-cause mortality in CAD and PAD patients, no relationship between obesity and mortality was observed in CVD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In obese patients, demand ischemia-induced claudication worsens their prognosis, independent from other compounding factors 1, 2 . Pathologically, demand ischemia in patients with PAD causes repetitive cycles of ischemic injury that exacerbate mitochondrial dysfunction, which induces oxidative stress 3 and gait deficits 4 .…”
Section: Introductionmentioning
confidence: 99%
“…103,104,106,108,109,111,113,115,116 All but three of the studies showed that greater total obesity (as measured by BMI) was associated with a greater frequency of adverse PAD-related outcomes. 110,115,117 Of the eight studies in which only BMI was assessed, data from five studies showed that total obesity increased the risk of adverse outcomes, such as a more-rapid decline in peak walking distance 109,111 or a cardiovascular event.…”
Section: Body Composition and Risk Of Padmentioning
confidence: 98%
“…110119 Only one study 112 used DEXA body density scans rather than body circumference measurements to assess abdominal adiposity. 110,111,113119 …”
Section: Body Composition and Risk Of Padmentioning
confidence: 99%
See 1 more Smart Citation